Assessment of Neurologic Disorders and Rare Intracranial Anomalies Associated With Cleft Lip and Palate. Issue 8 (November 2018) - Kucukguven, Arda; Calis, Mert; Topaloglu, Haluk; Ozgur, Figen
Abstract : Abstract: Accompanying neurologic disorders directly affect psychosocial development of cleft lip and/or cleft palate (CLP) patients and make it difficult for their family to look after them properly. The aim of this study was to investigate the diversity and the incidence of additional neurologic malformations in children with CLP and to evaluate their effects on cleft care. All patients who applied to our Cleft and Craniofacial Center between July 2014 and July 2017 were included in the study. Demographic and perioperative data such as gender, cleft type, syndromic status of the patient, associated neurologic anomalies, timing and duration of operation, hospitalization period, and follow-up period in the intensive care unit are all recorded. All patients received an interdisciplinary evaluation including pediatric neurology specialists in terms of mental and/or motor developmental delay, epilepsy, and other neurologic disorders. After detailed neurologic examination, 83 (3.8%) out of 2190 were reported as having a neurologic defect. The most leading neurologic disorder was found to be mental-motor retardation in 57 children followed by epileptiform disorders detected in 36 children. In 22 patients, rare intracranial pathologies were detected on magnetic resonance imaging. According to our results, having a neurologic pathology increases the need for intensive care unit stay by 5 times in these patients. There was statistically significant relationship between hospitalization period, age of cleft surgery, and neurologic pathologies in these patients. Neurologic disorders could complicate cleft care, cause delays in the planned surgery schedule, and increase perioperative and postoperative morbidity.